2005
DOI: 10.1007/11535331_13
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-textual Indexing for Geographical Search on the Web

Abstract: Abstract. Many web documents refer to specific geographic localities and many people include geographic context in queries to web search engines. Standard web search engines treat the geographical terms in the same way as other terms. This can result in failure to find relevant documents that refer to the place of interest using alternative related names, such as those of included or nearby places. This can be overcome by associating text indexing with spatial indexing methods that exploit geo-tagging procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
118
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(118 citation statements)
references
References 11 publications
0
118
0
Order By: Relevance
“…Future improvement of the presented approach would be to explore how to combine normalized spatial, temporal and thematic indexes and compute a unique relevancy scoring. Merging results for a geographic IR approach combining such different criteria is a recurring research question nowadays (Martins et al, 2008, Vaid et al, 2005.…”
Section: Ongoing and Future Workmentioning
confidence: 99%
“…Future improvement of the presented approach would be to explore how to combine normalized spatial, temporal and thematic indexes and compute a unique relevancy scoring. Merging results for a geographic IR approach combining such different criteria is a recurring research question nowadays (Martins et al, 2008, Vaid et al, 2005.…”
Section: Ongoing and Future Workmentioning
confidence: 99%
“…The papers about the SPIRIT (Spatially-Aware Information Retrieval on the Internet) project [13 17] are a very good starting point. In [16], the authors conclude that keeping separate text and spatial indexes, instead of combining both in one, results in less storage costs but it could lead to higher response times. More recent works can be broadly classi ed into two categories depending on how they combine textual and spatial indexes.…”
Section: Related Workmentioning
confidence: 99%
“…In our experiments to compare ST and TS it was found that TS indexing required slightly more space than ST but exhibited better query response times. In contrast the T scheme resulted in longer query times (up to double) but with very little storage overhead (Vaid et al, 2005).…”
Section: Building Document Indexesmentioning
confidence: 99%